2009
DOI: 10.1590/s0100-69162009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Biodigestão anaeróbia de dejetos de suínos com e sem separação da fração sólida em diferentes tempos de retenção hidráulica

Abstract: RESUMO:O objetivo deste trabalho foi avaliar o processo de biodigestão anaeróbia utilizando dejetos de suínos, com e sem separação da fração sólida, considerando-se diferentes tempos de retenção hidráulica. Para tanto, foram utilizados biodigestores tubulares semicontínuos abastecidos com água residuária de suinocultura, com e sem separação da fração sólida (CSFS e SSFS, respectivamente), manejados com tempos de retenção hidráulica (TRH) iguais a 36; 29; 22 e 15 dias. A eficiência dos tratamentos foi avaliada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…The similarities in the results for coliform reductions can be related to the shorter time interval among HRT employed in the current research when compared with the results shown by Orrico Junior et al (2010), who adopted an interval of 30 days, and another study of Orrico et al (2009) in which there was no difference among HRT with an interval of 7 days during digestion process of swine manure with and without separation of solid fraction in semi-continuous digesters operated at 15, 22, 29, and 36 days.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The similarities in the results for coliform reductions can be related to the shorter time interval among HRT employed in the current research when compared with the results shown by Orrico Junior et al (2010), who adopted an interval of 30 days, and another study of Orrico et al (2009) in which there was no difference among HRT with an interval of 7 days during digestion process of swine manure with and without separation of solid fraction in semi-continuous digesters operated at 15, 22, 29, and 36 days.…”
Section: Resultssupporting
confidence: 73%
“…As stated by Orrico Junior et al (2009), tubular digesters usually have high acid production in the input of the digester, which reduces the microorganism population due to the low pH in the beginning of the process.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, há também a possibilidade de venda dos serviços de sequestro de carbono, gerando os chamados "créditos de carbono" (BLEY JÚNIOR et al, 2009). O processo anaeróbio de degradação da matéria orgânica contida nos resíduos permite também a redução das demandas química e bioquímica de oxigênio e de sólidos (ORRICO JÚNIOR et al, 2009). Além disso, reduz as emissões de odores, amônia, metano e óxido nitroso (ANGONESE et al, 2007), bem como minimiza a população de microrganismos patogênicos dos materiais tratados devido às elevadas temperaturas que são atingidas no processo (LUSTE & LUOSTARINEN, 2010).…”
Section: Introductionunclassified
“…A partir da negociação dos créditos de carbono e utilização do biogás como fonte de energia, o produtor reduz seus custos de produção e consequentemente, há maior oportun idade de investimento em outros setores, sem se preocupar com o sistema de tratamento dos dejetos (Orrico et al 2009). De acordo com Bernstorff (2009), o projeto de MDL aplicado à suinocultura reduz as emissões de GEE's e promove créditos de carbono, demonstrando viabilidade técnica e econômica, sustentabilidade, e ainda boa rentabilidade financeira aos suinocultores.…”
Section: Introductionunclassified